Pleuropulmonary blastoma type 1 arising within a congenital bronchogenic cyst and involving the heart in a child - (:unkn) unknown (My University, 2001)
Rhabdomyosarcoma (RMS) arising within the lung of a child is an unusual phenomenon. Metastatic rhabdomyosarcoma involving the heart is also encountered rarely in children. Because extensive review of the literature failed to reveal any reported case of metastatic RMS to the heart from a primary arising within a congenital pulmonary cyst, the following case is being reported.
Keywords: Cardiac metastasis; Congenital bronchogenic cyst; Pleuropulmonary blastoma type 1